Impact and semi-static performance of thermoplastic composites - Chia, Justin Jun Hao (Nanyang Technological University, 2023)
This final year project aims to examine the impact and semi-static impact of thermoplastic composites, specifically Carbon Fiber Fabric-Reinforced Poylamide 6 thermoplastic composite laminates. Data obtained are then analyzed. Composites are first fabricated using the hot press compression process. Carbon Fiber Fabric (2x2 twill) is used while the polymer matrix PA6 is used. Mechanical experiments such as compression, 3-point flexural and impact are performed according to ASTM Standards to understand and characterize the properties of the material. A bandsaw is used to obtain the preferred specimen dimensions before mechanical testing is performed. Impact properties are obtained using a drop-weight impact event. Semi-static properties are obtained using compression and flexural test (3-point) tests. Test data obtained are used to plot stress-strain, force-displacement, and other types of graphs to obtain further information. Values like the ultimate tensile strength, yield point, maximum compressive stress, maximum flexural stress can be obtained from the graphs. The failure modes of the specimens are also investigated using the optical microscope. Parameters like the thickness of the laminate, which can vary due to manufacturing, can affect the performance of the material. The results from the various tests show that Carbon Fiber reinforced Poylamide6 thermoplastic composite laminates have good flexural, compression and impact properties. However, more tests and experiments can be conducted to improve these material as they have a common failing point in the weft and warp fiber bundles.